2012
DOI: 10.1029/2011jd016800
|View full text |Cite
|
Sign up to set email alerts
|

Eyjafjallajökull volcanic ash concentrations determined using Spin Enhanced Visible and Infrared Imager measurements

Abstract: , Eyjafjallajökull volcano in Iceland erupted a large amount of fine grained ash. Dispersion models and satellite data were used to identify the location of the ash cloud, but accurate quantitative forecasts of the concentrations could not be made. By using multispectral satellite measurements from the Spin Enhanced Visible and Infrared Imager (SEVIRI), it is shown that quantitative estimates of the mass loadings (g m À2 ) can be made with a detection limit $0.2 g m À2 , every 15 minutes. These data represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(187 citation statements)
references
References 55 publications
7
176
0
Order By: Relevance
“…An object is a group of adjacent grid cells that have an ash cloud loading value above a given threshold. Here, the threshold is defined as the typical ash detection limit 5 for most satellite retrievals (~ 0.2 g m -2 - Prata and Prata, 2012). Modeled ACL values below this threshold are omitted from all evaluation metrics.…”
Section: Evaluation Methods 15mentioning
confidence: 99%
“…An object is a group of adjacent grid cells that have an ash cloud loading value above a given threshold. Here, the threshold is defined as the typical ash detection limit 5 for most satellite retrievals (~ 0.2 g m -2 - Prata and Prata, 2012). Modeled ACL values below this threshold are omitted from all evaluation metrics.…”
Section: Evaluation Methods 15mentioning
confidence: 99%
“…Regulators therefore quickly decided to impose ash concentration limits which could be used to assess the ash hazard and allow, or prevent, implies that concentrations can be measured and forecast. Prata and Grant [64] and Prata and Prata [83] have shown that ash mass loadings can be determined from thermal infrared satellite data with a lower detection limit of about 0.2 g m −2 and a standard error of ±0.15 g m −2 and hence can meet the goal of determining concentration zones. To forecast concentrations however, requires accurate dispersion models and most importantly, knowledge of the eruptive behavior of the volcano, commonly referred to as the eruption "source" term [84].…”
Section: E Remote Sensing Of Volcanic Ashmentioning
confidence: 99%
“…Optically thin ash clouds and ash particles smaller than 0.2 µm may not be detected. Following this, the minimum detection limit of ash is considered to be in the range of 0.2-1.0 g m −2 Prata and Prata, 2012). Other factors, namely the thermal contrast between the ash and the underlying surface, satellite viewing angle, ash cloud height and the presence of other absorbers (e.g.…”
Section: Seviri Satellite Observationsmentioning
confidence: 99%